English for Occupational Purposes (EOP): Public and Environmental Health Employees’ Needs for English Language - MOHAMMED, Abuelgasim Sabah Elsiad (Politeknik Negeri Ujung Pandang, 2025)
English language is of great demand in all sectors and professional purposes are no exception. This is because learners of English language have become aware of the role that it plays in both academic and professional purposes. Employees who have a good command of English language can serve their area well, so it is necessary to cater for those employees’ needs for English language regardless their area of specialization to raise their employability. This paper aimed at analysing Public and Environmental Health (PEH) employees' needs for English for Occupational Purposes (EOP) to identify their use of English in their job, English usefulness to them, their present situation in English, and the most important language skills to them. The study adopted mixed method design. Data were collected through a questionnaire and a structured interview. The participants were 29 employees and two heads of departments at the Ministry of Health, Khartoum State, Sudan. Results showed that PEH employees frequently used English in their jobs. It is also revealed that English language was useful to the participants in their jobs. The employees’ proficiency was found to be good according to them, but it was regarded as average by the interviewees. All the language skills were considered important. The study recommends that the Ministry of Health, Khartoum State, should consider this NA results to prepare training courses in English for its employees.